Pengaruh Kinerja ESG dan Faktor Fundamental terhadap Harga Saham pada IDX ESG Leaders - Ketut Adi Juniasih; I Gede Agus Pertama Yudantara; I Putu Gede Diatmika (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to examine the influence of ESG performance and fundamental factors on share prices for companies included in the IDX ESG Leaders for the period 2021–2024. The study employs a quantitative approach using secondary data obtained from companies’ annual reports and sustainability reports. ESG performance is measured using the ESG Risk Rating, whilst fundamental factors are proxied by Return on Assets (ROA) and Debt to Equity Ratio (DER). The research sample was determined using purposive sampling and comprised 18 companies with a total of 72 observations. Data analysis was conducted using multiple linear regression. The results indicate that the ESG Risk Rating, ROA, and DER have a positive and significant effect on share prices. Simultaneously, ESG performance and fundamental factors have a significant effect on share prices. These findings suggest that investors do not merely consider financial factors but also take into account a company’s sustainability risk management when making investment decisions.